Willodeen eaudiobook - Applegate, Katherine (Listening Library, 2021)
From #1 New York Times bestseller Katherine Applegate, a singular middle-grade novel about a girl who risks everything to help her handmade bear when he comes to life. The earth is old and we are not, and that is all you must remember . . . Eleven-year-old Willodeen adores creatures of all kinds, but her favorites are the most unlovable beasts in the land: strange beasts known as “screechers.” The villagers of Perchance call them pests, even monsters, but Willodeen believes the animals serve a vital role in the complicated web of nature. Lately, though, nature has seemed angry indeed. Perchance has been cursed with fires and mudslides, droughts and fevers, and even the annual migration of hummingbears, a source of local pride and income, has dwindled. For as long as anyone can remember, the tiny animals have overwintered in shimmering bubble nests perched atop blue willow trees, drawing tourists from far and wide. This year, however, not a single hummingbear has returned to Perchance, and no one knows why. When a handmade birthday gift brings unexpected magic to Willodeen and her new friend, Connor, she’s determined to speak up for the animals she loves, and perhaps even uncover the answer to the mystery of the missing hummingbears. A timely and timeless tale about our fragile earth, and one girl’s fierce determination to make a difference.